2008
DOI: 10.1542/peds.2008-0582
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Consequences of Success in Pediatrics: Parental Health-Related Quality of Life—Results From the Care Project

Abstract: Parents of chronically ill children report a seriously lower health-related quality of life, which should receive attention and supportive care if necessary. A family-centered approach in pediatrics is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
131
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(146 citation statements)
references
References 30 publications
9
131
1
5
Order By: Relevance
“…Studies have shown high caregiving demands, [5][6][7] stress, 6,8,9 distress, 6,10 and lower health-related quality of life in caregivers. 11 Psychological outcomes have been found to be associated with the child's illness progression, perceived caregiving burden, social support, and financial burden. 5,6,9,10 However, survey and interview studies have also described components of DBMD caregiving that were perceived as beneficial, including an improved ability to appreciate life experiences and other positive coping strategies to manage the progressive disease course and chronic sorrow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown high caregiving demands, [5][6][7] stress, 6,8,9 distress, 6,10 and lower health-related quality of life in caregivers. 11 Psychological outcomes have been found to be associated with the child's illness progression, perceived caregiving burden, social support, and financial burden. 5,6,9,10 However, survey and interview studies have also described components of DBMD caregiving that were perceived as beneficial, including an improved ability to appreciate life experiences and other positive coping strategies to manage the progressive disease course and chronic sorrow.…”
Section: Introductionmentioning
confidence: 99%
“…20 We also measured coping self-efficacy, which assesses perceived ability to cope with challenges and threats. 21 On the basis of the importance of disease progression on caregiver outcomes in the DBMD literature, 6,11 the functional status of the child with DBMD was also assessed. This longitudinal study includes data from three survey points (baseline, year 1, and year 2) and aims to: (i) assess the associations between child's functional status and mothers' resilience, illness perceptions and coping self-efficacy; and (ii) determine whether child's functional status and mothers' personal attributes, illness perceptions, and coping self-efficacy as measured at baseline predict mothers' psychological adaptation to DBMD 2 years later.…”
Section: Introductionmentioning
confidence: 99%
“…Goldbeck (2006) found that parents of children with a chronic health condition, compared with parents of healthy children, reported a persistent impairment in most dimensions of perceived parental QoL. A study by Hatzmann, Heymans, Ferrer-i-Carbonell, van Praag, and Grootenhuis (2008) reported that, when compared to parents of healthy children, parents of chronically ill children had lower health-related QoL, with 45% of parents at risk for health-related QoL impairments, including difficulties in sleep, vitality, social functioning, daily activities, and emotions.…”
Section: Description Parents' Qol In the Context Of Pediatric Health mentioning
confidence: 99%
“…Another study in the Netherlands (Hatzmann et al, 2008) showed that parents of children with asthma, together with parents of children with sickle cell disease and metabolic diseases, reported lower QoL in a sample that was comprised of ten different conditions and a healthy comparison group. Differences in QoL among these parental groups may be difficult to explain due to the distinctive characteristics of the conditions and the heterogeneity of the samples in terms of disease severity and control.…”
Section: Specific Issues For Parents Of Children With Asthmamentioning
confidence: 99%
“…Severity of this deterioration is associated with many different sociocultural and economic factors as well as social support 3 . Many previous studies have assessed the influence of child's chronic disease on QoL and psychosocial well-being of parents and caregivers and demonstrated impairment in many aspects such as sleep, social functioning, daily activities, vitality, positive emotions, and depressive emotions [4][5][6][7][8] . Similar psychosocial outcomes have been observed in siblings of children with a chronic disease and they were reported to have higher anxiety and depression as well as lower cognitive development and peer activities 9 .…”
mentioning
confidence: 99%